X-ray Planning and Control in Gastrointestinal Stenting - Yu. A. Kozlova; Z. А. Bagateliya; D. D. Dolidze; I. Yu. Korzheva; G. М. Chechenin; Yu. V. Barinov; G. V. Danilov (Вестник рентгенологии и радиологии)
Background. Self-expandable metal stents (SEMS) are widely used in gastrointestinal (GI) tract obstructive lesions. Planning and stent placement control can be performed with using roentgenological, endoscopic or combined method. The choice of the method depends on doctor’s preferences and clinic’s traditions, but endoscopic one is used more often. Comparison of the above methods efficacy in a single-institution material was not found in the literature. Objective: to compare clinical and roentgenological results of GI stenting depending on the method used. Material and methods. In 2016–2021, 267 cases of GI stenting were performed in Botkin Municipal Clinical Hospital. In 70 (26%) of them an endoscopic method was used, in 97 (36%) – a roentgenological one, and in 100 (37%) – a combined one. All patients underwent X-ray control postop. Results were analyzed statistically. Results. The implementation of X-ray diagnostics solo or in combination with endoscopy in GI SEMS planning and placement provided better results in comparison with endoscopic method only. Total SEMS expansion was achieved in 99% of cases versus 79% after only endoscopic procedures, correct stent placement – in 98% and 75%, respectively, evacuation was restored in 98% and 70%, respectively. All differences were statistically significant (p < 0.001). It is evident that X-ray methods are not useful for preliminary marking in decompensated patients with GI stenosis. But after elimination of such cases from analysis, the difference between the groups remained statistically significant (p < 0.05). Conclusion. The data obtained substitute expediency of X-ray method solo or with endoscopic one. Significant improvement of the results can be referred to more exact preoperative selection of SEMS type and size with X-ray method.